Focal hole versus screw stimulation to prevent false negative results in detecting pedicle breaches during spinal instrumentation. Issue 4 (April 2019) - Troni, Walter; Benech, Carlo Alberto; Perez, Rosa; Tealdi, Stefano; Berardino, Maurizio; Benech, Franco
Highlights: Triggered EMG to detect pedicle screw malposition is burdened with frequent false negative results. Focal nerve root stimulation within the hole prevents inadvertent leakage of stimulating current. The technique is simple and fast, provides unambiguous results and prevents false negative results. Abstract: Objective: We describe a stimulus-evoked EMG approach to minimize false negative results in detecting pedicle breaches during lumbosacral spinal instrumentation. Methods: In 36 patients receiving 176 lumbosacral pedicle screws, EMG threshold to nerve root activation was determined using a focal probe inserted into the pilot hole at a depth, customized to the individual patients, suitable to position the stimulating tip at the point closest to the tested nerve root. Threshold to screw stimulation was also determined. Results: Mean EMG thresholds in 161 correctly fashioned pedicle instrumentations were 7.5 mA ± 2.46 after focal hole stimulation and 21.8 mA ± 6.8 after screw stimulation. Direct comparison between both thresholds in individual pedicles showed that screw stimulation was always biased by an unpredictable leakage of the stimulating current ranging from 10 to 90%. False negative results were never observed with hole stimulation but this was not true with screw stimulation. Conclusions: Focal hole stimulation, unlike screw stimulation, approaches absolute EMG threshold as shown by the lower normal limit (2.6 mA; p < 0.05) that borders the upper limit of threshold to direct activation of the exposed root. Significance: The technique provides an early warning of a possible pedicle breakthrough before insertion of the more harmful, larger and threaded screw.